How Does the Position in Business Group Hierarchies Affect Workers' Wages? - Hartmut Egger; Elke J. Jahn; Stefan Kornitzky (Institute of Labor Economics (IZA), 2021)
We merge firm-level data on ownership linkages with administrative data on German workers to analyze how the position in a business group hierarchy affects workers' wages. To acknowledge that ownership linkages are not onedirectional, we propose an index of hierarchical distance to the ultimate owner that accounts for the complex network structure of business groups. After controlling for unobserved heterogeneity, we find a positive effect of larger hierarchical distance to the ultimate owner of a business group on workers' wages. To explain this finding, we develop a monitoring-based theory of business groups. Our model predicts higher wages to prevent shirking by workers if a larger hierarchical distance to the ultimate owner is associated with lower monitoring efficiency.
Keywords: C23; J31; L23; 330; business groups; ownership networks; workers wages; difference-in-difference; hierarchical distance